Infectivity and pathobiology of H7N1 and H5N8 high pathogenicity avian influenza viruses for pigeons (Columba livia var. domestica). Issue 1 (2nd January 2021) - Sánchez-González, R.; Ramis, A.; Nofrarías, M.; Wali, N.; Valle, R.; Pérez, M.; Perlas, A.; Majó, N.
ABSTRACT: Avian influenza (AI) is one of the most important viral diseases in poultry, wildlife and humans. Available data indicate that pigeons play a minimum role in the epidemiology of AI. However, a degree of variation exists in the susceptibility of pigeons to highly pathogenic AI viruses (HPAIVs), especially since the emergence of the goose/Guangdong H5 lineage. Here, the pathogenesis of H5N8 HPAIV in comparison with a H7N1 HPAIV and the role of pigeons in the epidemiology of these viruses were evaluated. Local and urban pigeons ( Columba livia var. domestica ) were intranasally inoculated with 10 5 ELD50 of A/goose/Spain/IA17CR02699/2017 (H5N8) or A/Chicken/Italy/5093/1999 (H7N1) and monitored during 14 days. Several pigeons inoculated with H5N8 or H7N1 seroconverted. However, clinical signs, mortality, microscopic lesions and viral antigen were only detected in a local pigeon inoculated with H5N8 HPAIV. This pigeon presented prostration and neurological signs that correlated with the presence of large areas of necrosis and widespread AIV antigen in the central nervous system, indicating that the fatal outcome was associated with neurological dysfunction. Viral RNA in swabs was detected in some pigeons inoculated with H7N1 and H5N8, but it was inconsistent, short-term and at low titres. The present study demonstrates that the majority of pigeons were resistant to H5N8 and H7N1 HPAIVs, despite several pigeons developing asymptomatic infections. The limited viral shedding indicates a minimum role of pigeons as amplifiers of HPAIVs, regardless of the viral lineage, and suggests that this species may represent a low risk for environmental contamination. RESEARCH HIGHLIGHTS H7N1 and H5N8 HPAIVs can produce subclinical infections in pigeons. The mortality caused by H5N8 HPAIV in one pigeon was associated with neurological dysfunction. Pigeons represent a low risk for environmental contamination by HPAIVs.